Effects of environmental conditions on propanil degrading activity of Acinetobacter baumannii DT - Ngoc, Dau Thi Hong; Duc, Ha Danh; Thuy, Nguyen Thi Dieu (Academia Journal of Biology, 2020)
Effects of various environmental conditions on propanil degrading activity of Acinetobacter baumannii DT were investigated. Results showed that both propanil degradation and bacterial growth rate were reduced when bacteria were cultured in extreme conditions, such as high acidic or alkaline levels or high salinity. Moreover, the propanil degradation activity of A. baumannii DT decreased in contaminated water. The propanil dissipation rate was higher in herbicides-contaminated soil (treated soil) than in herbicide-free soil. In soil inoculated with A. baumannii DT, propanil removal was enhanced. Even though the propanil degrading activity of A. baumannii DT were reduced under extremely stressful conditions, this bacterium retained a good potential to degrade propanil in real environmental conditions.